Contribution à l’analyse de l’érosion intra-urbaine à Kinshasa (R.D.C.) - Thomas Wouters; Eléonore Wolff (Belgeo)
This study contributes to improve the understanding of the erosion process in an urban context. It proposes a visual interpretation key of the gullies, be they active or not, on a very high resolution satellite image. While the gullies are delineated, the urban context is analyzed on the image to identify the origin of each gully. These results are confronted with an exhaustive ground survey achieved by DGPS.